STATISTICAL ANALYSIS OF PIPE WEAR AND FAILURES IN HYDRAULIC SYSTEMS OF AGRICULTURAL MACHINERY CAUSED BY HYDRAULIC SHOCK (KIUT Publication, 2025)
This article presents a statistical analysis of the hydraulic shock phenomenon occurring in the hydraulic systems of agricultural machinery, particularly excavators and tractors, and its impact on the wear and failure of technical components, especially pipes and joints. In addition, the direct and indirect effects of hydraulic shock on energy efficiency are illustrated with quantitative indicators.